MANAJEMEN PEMBELAJARAN RAUDHATUL ATHFAL USWATUN HASANAH KABUPATEN BANJAR - Afirus Febian (Yayasan Akrab Pekanbaru, 2018)
Raudhatul Athfal (RA) Uswatun Hasanah, as the main Raudhatul Athfal in South Kalimantan Province, should properly implement the Management of Kindergarten School and Government Regulation of National Education Number 58 Year 2009, so that it can become a good example for other Raudhatul Athfals. The objectives of the research were to find out the teaching and learning management of kindergarten at RA Uswatun Hasanah in Banjar Regency. The data were analyzed by models of Miles and Huberman, namely the data reduction, presentation, and verification.The conclusions of the research were: the teaching and learning management did not optimally implement the Content Standard, Process, and Assessment in Government Regulation of National Education Number 58 Year 2009. Keywords: School Management, Kindergarten, Raudhatul Athfal.